Pelatihan Keterampilan Berbicara Permasalahan Medis Berbantuan Teknik Role Play Bagi Mahasiswa Program Studi Profesi Apoteker Universitas Perintis Indonesia - Bahardur, Iswadi; Putri Dian Afrinda; Sri Mulyani Rusli (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2025)
Strong speaking skills are an essential component of pharmaceutical practice, particularly when delivering medication information with appropriate professionalism and empathy toward patients. However, oral communication training in pharmacist professional education often remains overlooked. In response to this gap, this community engagement program aimed to enhance the speaking abilities of students in the Apothecary Professional Program at Universitas Perintis Indonesia through the use of the role play technique. Ten students participated in the training, which was conducted in two sessions: a theoretical session and a practical session focusing on speaking skills related to pharmaceutical issues through role play. During the practice session, eight pharmacist–patient communication scenarios were designed and enacted by the participants. Evaluation was carried out using an observation checklist covering five main indicators: sentence structure, diction, intonation, therapeutic messaging, and patient responsiveness. The results demonstrated a significant improvement in the students’ ability to convey information orally in a more communicative, clear, and empathetic manner. The role play technique proved effective not only in enhancing technical speaking skills but also in fostering students’ awareness of the importance of humanistic and professional communication in pharmacy practice. Consequently, integrating this method into the curriculum emerges as a strategic approach to preparing future pharmacists who are both clinically competent and sensitive to patients’ needs.